Right Table, Wrong Idioculture: Examining the Impacts of TTRPG-specific Media at the Player Table Level - Duddy, Michael; Rosnau, Benjamin (New Explorations)

(untitled) (New Explorations Association, 2024)
Over the past decade and a half, there has been an explosion in the quantity and availability of media focused on tabletop role-playing games (TTRPGs). Episodes of highly-produced actual play series like Critical Role and Dimension 20 regularly get millions of views online and have spawned hundreds, if not thousands, of similar programs. Type in “Dungeons & Dragons” or “tabletop role playing” into your search engine of choice, and you will find copious amounts of meta content covering nearly every aspect of the hobby. This wide range of content caters to a broad audience — from the beginner player with zero real-world experience, all the way to the grizzled veteran Dungeon Master. The popularity of these media has brought more players to the game and has made it easier for new players to become socialized into the subculture. Currently, little research exists on the impacts of these media on the quality of players' games. Central to our discussion is Sidhu and Carter’s concept of “pivotal play,” wherein moments transcend the game and deeply impact the players even after they walk away from the table. We propose a framework necessary for moments of pivotal play to emerge, encompassing three layers of socialization crucial for each player: game competency, subcultural competency, and comradery. Through five qualitative, in-depth interviews with experienced TTRPG players, we sought to understand if this explosion of TTRPG-specific media has changed how players play TTRPGs. As a result of our research, we identify five key impact areas and suggest a new term (parasocial idioculture) to describe how actual play media may affect the process of player socialization.